2014
DOI: 10.1021/jp411701g
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Aggregates in Aqueous Solutions of Polyion–Surfactant Ion Complex Salts and a Nonionic Surfactant

Abstract: Water-soluble aggregates based on two polyion-surfactant ion "complex salts", consisting of hexadecyltrimethylammonium (C16TA(+)) and polyacrylate (PA(-)) with either 25 or 6000 repeating units, with added nonionic surfactant octaethylene glycol monododecyl ether (C12E8) have been investigated. A previous phase study has shown that added C12E5 or C12E8 can solubilize complex salts in aqueous systems, and that increasing the poly(ethylene oxide) chain length of the nonionic surfactant and/or decreasing the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 62 publications
(106 reference statements)
0
22
0
2
Order By: Relevance
“…They found that above a certain nonionic-to-ionic amphiphile ratio the insoluble complex salt can be resolubilized due to the largely increased hydrophilicity of the formed P/S mix complexes. 12 −14 In contrast to the previously mentioned studies, we have shown recently that the addition of n-dodecyl-β-D-maltoside (C 12 G 2 ) can both enhance and suppress the association between poly(diallyldimethylammonium chloride) (PDAD-MAC) and sodium dodecyl sulfate (SDS). 15,16 Based on these observations, a novel approach was proposed according to which the addition of an uncharged cosurfactant has two distinct impacts on the P/S association.…”
Section: Introductionmentioning
confidence: 93%
“…They found that above a certain nonionic-to-ionic amphiphile ratio the insoluble complex salt can be resolubilized due to the largely increased hydrophilicity of the formed P/S mix complexes. 12 −14 In contrast to the previously mentioned studies, we have shown recently that the addition of n-dodecyl-β-D-maltoside (C 12 G 2 ) can both enhance and suppress the association between poly(diallyldimethylammonium chloride) (PDAD-MAC) and sodium dodecyl sulfate (SDS). 15,16 Based on these observations, a novel approach was proposed according to which the addition of an uncharged cosurfactant has two distinct impacts on the P/S association.…”
Section: Introductionmentioning
confidence: 93%
“…The structural stability and composition of the mixed polymer-surfactant complex formed is dictated by different contributions, e.g., polymer architecture, 77 or by addition of nonionic surfactants. 11 The electrostatic interactions within the complexes, which are optimized when all the charged groups are reciprocally neutralized, play here an important role.…”
Section: Electrophoretic Mobility Measurementsmentioning
confidence: 99%
“…At compositions comparable to those used here it was concluded that approximately 20% of the C 12 E 8 resides in polymer-free micelles. 6,29 A sample where DB is completely degraded, on the other hand, contains C 12 E 8 , PA, and the hydrolysis products of DB, i.e., decanol and betaine. Because the electrostatic attraction to the micelles is here eliminated, the PA is released from the aggregates and can be considered to be free in solution.…”
Section: Release Of Pa From the Solubilized Mixed Aggregatesmentioning
confidence: 99%
“…The apparent sizes of the mixed aggregates can also be compared to the apparent R H for the aforementioned stoichiometric complex of C 16 TA + and PA short (of the same quality as used in the present study) solubilized by C 12 E 8 , which was determined by dynamic light scattering to be 3.4 nm. 29 Neither the R H of the mixed aggregates with PA nor the fraction of C 12 E 8 residing in these are known and it is thus not possible to make any detailed assessments of the sizes or relative fractions of the mixed aggregates or the excess micelles. However, if one considers the degrees of polymerization of the PAs used and the global compositions of the samples, it is possible to estimate tentative sizes of the mixed aggregates formed with PA short and PA long , respectively, and then compare these to the experimental apparent R H to obtain additional understanding of the samples.…”
Section: Release Of Pa From the Solubilized Mixed Aggregatesmentioning
confidence: 99%